The foundation history of the city in the Center of Asia. To the 95th anniversary of Belotsarsk - Uryankhaysk - Krasnyi - Kyzyl - Bondarenko, Tatyana A. (The New Research of Tuva, 2009)
Article reveals the history of how Kyzyl - capital of Tuva - had been found, basing on the archival documents.
Keywords: History; documents; Belotsarsk; Kyzyl; certificates; Uryankhay